KEY DRIVER AND BARRIER OF RUBBER COMPOUND TECHNOLOGY ADOPTION AMONG FINISHED RUBBER PRODUCT SMES: A MULTIPLE CASE STUDIES - Kristiyanto, Ari; Anggraeni, Elisa; Sailah, Illah (Jurnal Teknologi Industri Pertanian, 2025)
This study investigates the drivers and barriers to the adoption of rubber compounding technology among small and medium enterprises (SMEs) in Indonesia's finished rubber product sector. As the world's second-largest natural rubber producer, Indonesia has significant potential for growth in this sector. However, technology adoption in SMEs faces several challenges, primarily due to resource constraints and perceptions of technology, organizational, and environmental conditions. A qualitative multiple case study method was employed, with data collected through semi-structured interviews with business owners or top management. Analysis, conducted through within-case and cross-case comparisons, revealed that while technological complexity acts as a significant barrier, human expertise is a key driver of successful adoption. The findings highlight the importance of strategic investment in human capital and phased implementation strategies to reduce complexity. These insights contribute to discussions on technology adoption success factors in SMEs. Managerially, they provide policymakers and industry leaders with practical guidance on supporting SMEs to enhance competitiveness and drive sector growth. Keywords: technology adoption, SMEs, diffusion of technology, Technology-Organization-Environment, multiple case study